Statistical Learning in the Visuomotor Domain and Its Relation to Grammatical Proficiency in Children with and without Developmental Language Disorder: A Conceptual Replication and Meta-Analysis. Issue 4 (1st October 2020) - Lammertink, Imme; Boersma, Paul; Wijnen, Frank; Rispens, Judith
ABSTRACT: Children with Developmental Language Disorder (DLD) have difficulties acquiring the grammatical rules of their native language. It has been proposed that children's detection of sequential statistical patterns correlates with grammatical proficiency and hence that a deficit in the detection of these regularities may underlie the difficulties with grammar observed in children with DLD. Although there is some empirical evidence supporting this claim, individual studies, both in children with and without DLD, vary in the strength of their reported associations. The aim of the present study is therefore to evaluate the evidence for the proposed association. This is achieved by means of (a) a conceptual replication study on 35 children with DLD and 35 typically developing children who performed the serial reaction time task and a test of grammatical proficiency and (b) a meta-analysis over 19 unique effect sizes, which collectively examined the serial reaction time task – expressive grammar correlation in 139 children with DLD and 573 typically developing children. Both outcomes provide no evidence for or against the existence of the proposed association. Neither do they provide evidence for a difference in the strength of the association between both groups of children.